2004
DOI: 10.1038/sj.npp.1300597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Cigarette Smoke Exposure on Body Weight, Appetite and Brain Neuropeptide Y in Mice

Abstract: Although nicotinic receptors have been demonstrated in hypothalamic appetite-regulating areas and nicotine administration alters food intake and body weight in both animals and humans, the mechanisms underlying the effects of smoking on appetite circuits remain unclear. Conflicting effects of nicotine on the major orexigenic peptide, neuropeptide Y (NPY), have been observed in the brain, but the effects of smoking are unknown. Thus, we aimed to investigate how cigarette smoking affects body weight, food intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
107
5
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 64 publications
18
107
5
9
Order By: Relevance
“…This oxidative stress may cause a local inflammatory response, with higher IL12, tumour necrosis factor-a, neutrophils, macrophages and lymphocytes that may be related to the morphological changes observed (Zheng et al 2009, Braber et al 2010. Taken together, the morphological changes of maternal lung and high cotinine levels in serum and milk confirm the effectiveness of smoke (Arai et al 2001, Chen et al 2005, we observed that S dams did not present changes of these parameters throughout the lactation period. A simplistic explanation for this fact could be the relatively short period of smoke exposure (18 days of lactation).…”
Section: Discussionsupporting
confidence: 65%
“…This oxidative stress may cause a local inflammatory response, with higher IL12, tumour necrosis factor-a, neutrophils, macrophages and lymphocytes that may be related to the morphological changes observed (Zheng et al 2009, Braber et al 2010. Taken together, the morphological changes of maternal lung and high cotinine levels in serum and milk confirm the effectiveness of smoke (Arai et al 2001, Chen et al 2005, we observed that S dams did not present changes of these parameters throughout the lactation period. A simplistic explanation for this fact could be the relatively short period of smoke exposure (18 days of lactation).…”
Section: Discussionsupporting
confidence: 65%
“…This is partly in line with our current and previous data, showing that 24 wk-but not 4 wk-CS exposure induces significant weight loss (51). The difference between our findings and the studies by Chen et al (47)(48)(49)(50) are most likely due to interstrain differences. These investigators used BALB/C mice, whereas in the current study C57BL/6 and C57BKS mice were used.…”
Section: Figuresupporting
confidence: 52%
“…Recent studies from Chen et al (47)(48)(49)(50) investigated the relationship among smoking, neuropeptide Y, and weight loss and demonstrated that short-term (4 d) (47) and long-term (5, 7, and 12 wk) (48-50) CS exposure led to a significant reduction in body weight and systemic leptin concentration. This is partly in line with our current and previous data, showing that 24 wk-but not 4 wk-CS exposure induces significant weight loss (51).…”
Section: Figurementioning
confidence: 99%
“…Previous investigations have demonstrated that short-term cigarette smoke exposure leads to a reduction in body weight and food intake, suggesting a mechanism of alteration in activity of hypothalamic neuropeptide Y by nicotine. [21,22] Others suggest that smoking-related health risks may increase during periods of significant weight loss. [23] In unanesthetised animals, weekly Na + excretion decreased in nicotine-infused animals but increased progressively in animals administered methylated spirits alone and in combination with nicotine (see Table 1).…”
Section: Discussionmentioning
confidence: 99%